Examining the Impact of Artificial Intelligence Integration in ESP Tourism and Hospitality Education on Students’ Critical Thinking Skills - Siska Amelia Maldin; Dailami Dailami; Tito Pratama; Yudha Wardani; Arina Luthfini Lubis; Yoffie Kharisma Dewi (Journal of English Language and Education, 2026)
Artificial Intelligence (AI) integration such as ChatGPT, Grammarly, QuillBot, AI-based language learning platforms, and automated feedback applications has become increasingly important in higher education, particularly in English for Specific Purposes (ESP) tourism and hospitality learning. However, limited studies have specifically examined the influence of AI integration on students’ critical thinking skills in ESP tourism contexts. This study aimed to investigate AI integration influences students’ critical thinking skills in ESP tourism and hospitality education. The study employed a quantitative descriptive design involving 113 students of tourism study program selected through purposive sampling. Data were collected using questionnaires and analyzed through validity, reliability, and simple linear regression analyses using SPSS 25. The findings revealed that AI integration significantly influenced students’ critical thinking skills with an R Square value of 0.360 and significance level of 0.000. The study concludes that AI integration positively contributes to students’ critical thinking development in ESP tourism.